Small but mighty: unlocking the catalytic power of individual iridium atoms on titanium oxide - Molina-Torres, Mariana; Hernández-Cristóbal, Orlando; Mendoza-Cruz, Ruben (Frontiers in Nanotechnology, 2023)
Single atom catalysts (SACs) have emerged as a rapidly developing field of catalysis research, with great potential for improving the efficiency and selectivity of many chemical reactions. SACs consist of isolated metal atoms dispersed on a support material, providing a unique and welldefined atomic structure and composition, allowing for precise control over their properties. In particular, iridium SACs are applied in numerous reactions, from electrocatalytic to photocatalytic applications. By the other hand, titanium oxide is a semiconductor with important applications as a reducible support for different catalyst, widely used in different reactions because of its high activity and stability. This review covers recent developments and frontiers in the particular system of Ir -TiO2 SACs. It discusses the importance, synthesis, characterization techniques such as XPS, STEM, DRIFT, and XAS, and the applications of Ir -TiO2 SACs. The review also explores the stability and durability of single-atom catalysts and the importance of understanding their structure-activity relationships to optimize their performance. A key dimension emphasized in this review is the importance of investigating the iridium-titania system. Iridium exhibits superior properties compared to other metals, particularly in maintaining stability as a single atom, owing to its resistance to sintering. Gaining a comprehensive understanding of and optimizing these factors are instrumental in unlocking the full potential of Ir -TiO2 SACs. This route offers a promising trajectory towards enhancing catalytic performance across a spectrum of applications and facilitating the discovery of novel chemical reactions.